Psoriasis and Cardiovascular Disease: A Literature Review of Relationships and Causes - Amatillah, Athiyah; Hayunanto, Bambang Dwi; Halim, Alviannur (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Psoriasis and cardiovascular disease share a complex interrelation mediated by chronic inflammation. Epidemiological data reveal higher cardiovascular risks in psoriasis patients, including diabetes and atherosclerosis. Pathophysiologically, inflammatory cytokines play a pivotal role. Genetic, lifestyle, and psychological factors exacerbate this link. Anti-inflammatory therapies, notably TNF-α inhibitors, demonstrate potential in mitigating cardiovascular risk. However, pharmacotherapy selection necessitates cautious consideration, especially regarding biologic agents' impact on cardiovascular health. Management entails tailored approaches ranging from topical treatments to biologics, adjusted to disease severity and individual response. Understanding this relationship fosters personalized treatment strategies. Further research is imperative for validation and deeper mechanistic insights, enhancing prevention and management paradigms for affected individuals.